2020
DOI: 10.1002/htj.21858
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation minimization and nonlinear heat transport in MHD flow of a couple stress nanofluid through an inclined permeable channel with a porous medium, thermal radiation and slip

Abstract: Irreversible losses and heat transport in a magnetohydrodynamic flow of a viscous, steady, incompressible, and fully developed couple stress Al 2 O 3-water nanofluid through a sloping permeable wall channel with porous medium and under the effect of radiation heat flux and slip were analyzed. The fundamental equations were solved numerically by using Runge-Kutta together with the shooting technique and the results were in qualitative agreement with an exact solution obtained for a limit case. The impacts of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The irreversibility analysis of magnetohydrodynamic Casson nanofluid flow through an inclined microporous channel with the influence of nonlinear thermal radiation is discussed. Following the work presented by Rosales et al [32] and López et al [35], the following selection of parameters is held constant throughout the examination unless otherwise expressed. (𝐸𝑐 = 𝑅𝑒 = 𝑃 = 𝐵𝑟 = 𝐷𝑎 = 𝑃𝑟 = 1, 𝛽 = 𝑀 = 𝐵𝑖 = 𝐺𝑟 = 0.5, 𝑅𝑑 = 𝜃 ℎ = 1.5, 𝛾 = 𝜋∕3, 𝑄 = 0.2, 𝑆 = 0.1, 𝜙 = 0.1).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The irreversibility analysis of magnetohydrodynamic Casson nanofluid flow through an inclined microporous channel with the influence of nonlinear thermal radiation is discussed. Following the work presented by Rosales et al [32] and López et al [35], the following selection of parameters is held constant throughout the examination unless otherwise expressed. (𝐸𝑐 = 𝑅𝑒 = 𝑃 = 𝐵𝑟 = 𝐷𝑎 = 𝑃𝑟 = 1, 𝛽 = 𝑀 = 𝐵𝑖 = 𝐺𝑟 = 0.5, 𝑅𝑑 = 𝜃 ℎ = 1.5, 𝛾 = 𝜋∕3, 𝑄 = 0.2, 𝑆 = 0.1, 𝜙 = 0.1).…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…[1] and Rosales et al. [32]): Cf=1+1βdudy,Nu=aknf+16σT33k()dTdyy=0kffalse(Tfalse(y=0false)Tbfalse).$$\begin{align} C_f &= {\left(1 + \frac{1}{\beta} \right)} {\left(\frac{d u^{\prime}}{dy^{\prime}} \right)},\nonumber\\ Nu &= - \frac{a {\left(k_{nf} + \frac{16 \sigma T^{3}}{3k^{*}} \right)} {\left(\frac{d T}{d y^{\prime}} \right)}_{y^{\prime}=0}}{k_{f} (T_{(y^{\prime}=0)} - T_{b})}. \end{align}$$Equation () dimensionless form is given as Cf=1+1βdUdχ,Nu=knfkf+Rdfalse[(θh1)θ+1false]3()dθdχχ=0θ(χ=0)01Uθdχ01Udχ,$$\begin{align} C_f &= {\left(1 + \frac{1}{\beta} \right)} {\left(\frac{d U}{d \chi} \right)},\nonumber\\ Nu &= - \frac{{\left(\frac{k_{nf}}{k_{f}} + Rd [(\theta _{h} - 1) \thet...…”
Section: Aspects Of Physical Interestmentioning
confidence: 99%
“…According to the results, boosting the radiation parameter lowers the temperature distribution, while boosting the pressure term raises the velocity distribution. Intending to identify the conditions under which entropy generation and nonlinear heat transfer are minimised, Rosales et al [24] analysed the impact of a magnetic field on couple stress nanofluid in an inclined channel. Using the Runge-Kutta method and a shooting technique, the initial equations were solved.…”
Section: Introductionmentioning
confidence: 99%
“…Intending to identify the conditions under which entropy generation and nonlinear heat transfer are minimised, Rosales et al. [24] analysed the impact of a magnetic field on couple stress nanofluid in an inclined channel. Using the Runge–Kutta method and a shooting technique, the initial equations were solved.…”
Section: Introductionmentioning
confidence: 99%
“…where, The local volumetric rate of entropy generation SG for the configuration under study is found as (following the authors in [9,12,13,20,25,33,34])…”
mentioning
confidence: 99%